Mirza Qaleech Baig: Representative of five famous writer of Urdu (In the light of Sindhi literature history books in Urdu) - Pathan, Muhammad Arif; Hussain, Shazra (sourcecoder, 2023)
The title of this research article is ‘Mirza QaleechBaig: Urdu Arkan-e-Khamsa ka Numayndah’ (Urdu Zuban me Likhigayee Sindhi Adabi Tawareekh ki Roshani me) which has been represented the Mirza QaleechBaig’s Literary services like as Urdu Arkan-e-Khamsa and also considered with the opinion of history writers of Sindhi literature in urdu& Sindhi languages. This article will be helpful to understand the history books of Sindhi Literature and as well as familiar to the regional literary efforts of the Mirza QaleechBaig in Urdu language۔